EVALUASI PROGRAM PENCEGAHAN PENGENDALIAN INFEKSI MENGGUNAKAN MODEL CIPP DI RUMAH SAKIT UMUM KOTA TANGERANG SELATAN - Noor, Sirajudin; Nurahmawati, Zihan (Jurnal Keperawatan Widya Gantari Indonesia, 2024)
Infection prevention and control programs have a high urgency to provide preventive, curative, and comprehensive health services to the community. Evaluation of the IOP program is needed to analyze the series of programs that have been implemented towards the quality of the IOP program. The researcher aims to evaluate the implementation of the infection prevention and control program at the South Tangerang City Hospital. This study used a qualitative method with the Contex Input Process Product (CIPP) evaluation model approach. Data was collected by means of in-depth interviews, observation using the Hospital National Accreditation Standard (SNARS) 2022 observation sheet. The informants in this study were 5 people, 2 participants were officers in the PPI committee of South Tangerang General Hospital and 3 other people were the target recipients and program implementers. Data were analyzed with 3 stages, namely data reduction, data presentation, and conclusion drawing. Data validity used triangulation techniques.